Biogenic amine and microfloral profiling of Indian mackerel, Rastrelliger kanagurta cuvier during storage - Chong , Cheong Yew (2012)
Indian mackerel is the most common marine fish in Malaysia and is potentially associated with histamine poisoning incidence. However, no literature is available on the profile of biogenic amines in different storage conditions. Biogenic amines, biochemical, microbiological changes and sensory evaluation were investigated in Indian mackerel stored at different temperature and modified atmosphere packaging. Dominant spoilage microflora was identified in fish stored in air, vacuum packaging and 100%. Indian mackerel was subjected to storage at ambient temperature (25-29°C),chilled temperature (5 °C) and ice temperature (0 °C). Biogenic amines and various biochemical analysis such as pH, total volatile basic nitrogen and amino acids were carried out. All amines except for spermidine and spermine increased significantly during storage at ambient and chilled temperatures. The concentration of histamine reached the FDA acceptable limit after 16 hours at ambient temperature and 5 days at chilled temperature. Proper icing procedure retarded the formation of histamine effectively. This study confirmed the relationship between histidine and formation of histamine at ambient and chilled temperature. As storage time progressed, the amines forming bacteria grew significantly except for that stored in ice. The Indian mackerel was stored in air, vacuum packaging, 30% CO2/5% O2/65% N2, 60% CO2/5% O2/ 35% N2, 80% CO2/5% O2/ 15% N2 and 100% CO2 at chilled temperature (5°C) for 12 days. Each biogenic amine responded differently to a different level of CO2. High level of CO2 (≥60% CO2) was effective in retarding the formation of histamine in Indian mackerel. Fish stored in vacuum packaging and 30% CO2/5% O2/ 65% N2 tended to have a high concentration of histamine and tyramine. Vacuum packaging and all modified atmosphere packaging treatments were effective in reducing the pH and total volatile basic nitrogen. This study confirmed that the inhibitory effect of CO2 increases as the level of CO2 increases. The aerobic psychrotrophic bacteria were responsible for the formation of cadaverine and putrescine during the later stage of storage. The application of modified atmosphere packaging improved the shelf life of Indian mackerel. According to sensory evaluation, the fish was still acceptable by the panelists when stored for 5 days in air, 7 to 8 days in vacuum packaging and 30% CO2/5% O2/ 65% N2, 9 days in 60% CO2/5% O2/ 35% N2, 10 to 11 days in 100% CO2. In general, Aeromonas sp. was found as the dominant spoilage microflora during storage in air, vacuum packaging and 100% CO2. However, the diversity of microflora changed toward the end of the storage. The microbial diversity was directed to Pseudomonas sp. and enterobacteria in fish stored in air. In vacuum packaging, the prevalence of lactic acid bacteria and enterobacteria increased at the end of storage. The findings of the present study could contribute to the knowledge of food safety in controlling biogenic amine formation and microbial ecology in tropical fish. Aerobic plate count and total volatile basic nitrogen were correlated well with histamine at different storage temperature and atmosphere. Among the biogenic amines, cadaverine or cadaverine + putrescine can serve as good freshness indicator. A higher percentage of CO2 and a lower percentage of O2 in modified atmosphere packaging can be applied successfully in retarding the formation of histamine.